Preparation of radiochemically pore-filled polymer electrolyte membranes for direct methanol fuel cells - Nasef, M. M.; Zubir, N. A.; Ismail, A. F.; Dahlan, K. Z. M.; Saidi, H.; Khayet, M. (Elsevier Science B.V., 2006)
Polymer electrolyte pore-filled membranes, for possible use in direct methanol fuel cells (DMFCs), have been prepared by radiochemical grafting of styrene into porous poly(vinylidene fluoride) (PVDF) films using simultaneous irradiation with an electron beam (EB) followed by a sulfonation reaction. The physico-chemical properties of the obtained polystyrene sulfonic acid pore-filled membranes are evaluated using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), ac impedance, and a methanol diffusion cell. The effects of variation of the grafting yield (Y%) on the ionic conductivity and the methanol permeability of the membranes are investigated. The ionic conductivity of the membranes increases with increase in Y% and exceeds that of the perfluorinated ionomer membrane, Nafion 117, at a grafting yield of 46%. The methanol permeability of 40 and 46% pore-filled membranes is lower than that of Nafion 117 by 53 and 71%, respectively. The performance characteristic factor suggests that these membranes are potential candidates for DMFC applications.